KORELASI STATUS GIZI, ASUPAN ZAT BESI DENGAN KADAR FERITIN PADA ANAK USIA 2-5 TAHUN DI KELURAHAN SEMANGGI SURAKARTA - Sunarti, .; Nugrohowati, Annta Kern (Universitas Ahmad Dahlan, 2014)
AbstractBackground : Undernutrition was still a problem of public health in Indonesia. Prevalence of undernutrition in under five years old based weight for age is 17.9 %. Undernutrition in children usually happened acute and cronic deficiency of macronutrient and have effect micronutrient deficiency. Iron deficiency anemia is one of micronutrient deficiency that common problems in under five children. Prevalence of iron deficiency anemia is 27.5 %. This prevalence is very high. This research wants to know about correlation z score weigh for age and iron intake with ferritin level in children 2-5 year old.Objective : Objective of this research was to know correlation about z score weight for age and iron intake with ferritin level in children 2-5 year old.Method : The research method used in this study was cross-sectional study. Z score weight for age was measured by using antropometry. Iron intake was measured by using 24-hour food recall method and ferritin level was maesured by using ellysa method. The data was analyzed by multiple linier regression. Result : Iron intake had contribution to ferritin level about 1.747 µg/L with p value 0.007. Z score weight for age had no contribution to ferritin level in children 2-5 year old with p value 0.972 Conclution : Iron intake had contribution of ferritin level and z score weight for age had no contribution with ferritin level. Keyword : Zat Besi, feritin, undernutrition